2017
DOI: 10.1590/1678-4499.160
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of cabbage lines reveals resistance to infection by Cucumber mosaic virus

Abstract: as moderately susceptible and 3 were susceptible to the CMV-BA isolate. These plants exhibited various symptoms and accumulated high levels of virus titer. However, the results showed that 17 lines had high resistance, 12 were found to be resistant and 10 were found to be moderately resistant to the CMV. The lines that showed high levels of resistance to the virus in this study could be used as sources of CMV resistance in cabbage breeding programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…In addition, N translocation from leaves to grains is high. Several studies conducted under NT systems in Brazil have shown an increase in N-leaf concentration of maize (Caires & Milla, 2016;Soratto, Silva, Cardoso, & Mendonça, 2011) and wheat (Los Galetto et al, 2017;Teixeira Filho, Buzetti, Andreotti, Arf, & Sá, 2011) with increasing N rate application. In grains, an increase in N concentration was also obtained with top dressing N fertilization compared to N application only at sowing of maize (Pedrosa et al, 2020) and with increasing N rate application in top dressing of wheat (Los Galetto et al, 2017;Rodrighero et al, 2015).…”
Section: Amendment Effects On Soil and Plant Nutritionmentioning
confidence: 99%
“…In addition, N translocation from leaves to grains is high. Several studies conducted under NT systems in Brazil have shown an increase in N-leaf concentration of maize (Caires & Milla, 2016;Soratto, Silva, Cardoso, & Mendonça, 2011) and wheat (Los Galetto et al, 2017;Teixeira Filho, Buzetti, Andreotti, Arf, & Sá, 2011) with increasing N rate application. In grains, an increase in N concentration was also obtained with top dressing N fertilization compared to N application only at sowing of maize (Pedrosa et al, 2020) and with increasing N rate application in top dressing of wheat (Los Galetto et al, 2017;Rodrighero et al, 2015).…”
Section: Amendment Effects On Soil and Plant Nutritionmentioning
confidence: 99%
“…However, the nutrient contents in corn grains used as reference values in Brazil have been practically the same for over 20 years (Raij et al 1996;Cantarella and Duarte, 2004), and are based on old studies, such as those of Andrade et al (1975a,b), Hiroce et al (1989), and Coelho and França (1995). The diversity of plant materials and heterogeneity of management types can influence grain nutrient contents (Carlone and Russel, 1987;Ciampitti and Vyn, 2013;Caires and Milla, 2016). Recent results of grain nutrient contents indicate a possible reduction in N and K (Resende et al, 2012), although the high variation among environments and/or cultivars hampers a joint interpretation that would enable conclusions about the new reference values.…”
Section: Introductionmentioning
confidence: 99%
“…Ear diameter, in turn, is often related to grain filling and to the number of grain rows per ear (Ohland et al, 2005). According to studies, the number of rows per ear is a component dependent on the plant's genetic potential and on environmental conditions (Valderrama et al, 2011;Caires & Milla, 2016). For this reason, there was no interaction between N sources and application times in this study.…”
Section: Days After Sowingmentioning
confidence: 63%